Size Doesn't Matter: The Complicated Relationship between national offshore Oil Spill Events, Framing, and Policy. Issue 1 (March 2016) - Greer, Alex; Best, Eric
Understanding issue framing in the context of offshore spills is important because it shapes how media, the public, interest groups, and politicians define failure and propose acceptable solutions that, through agenda setting, become policy. This paper explores the complex relationship between agenda setting, framing, and attention garnered by U.S. offshore oil spill events and resulting federal policy. To examine this important issue, this study considers nine major offshore oil spills in U.S. waters, exploring the attention paid to each spill and any resulting policy changes. Analysis of these past spills suggests that the size of offshore oil spills is not indicative of the amount of media and policy attention that an event will trigger. In contrast, framing is an important element of the reaction to these rare maritime disasters. While spills in U.S. waters large enough for inclusion in this study were limited, results support previous findings that suggest that location is one of the most important factors in this complicated relationship.